2009
DOI: 10.1007/s10562-009-9900-7
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Deoxygenation of Methyl-Octanoate and Methyl-Stearate on Pt/Al2O3

Abstract: The deoxygenation of methyl octanoate and methyl stearate over alumina-supported Pt was studied in both the vapor phase in a flow reactor and in the liquid phase in a semibatch reactor. The conversion of both methyl esters resulted in hydrocarbons with one carbon less than the fatty acid of the corresponding ester as the dominant products. In the vapor phase, acid and other oxygenates were observed in low concentrations, but they were not detected when the reaction was conducted in the liquid phase. Under He, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(87 citation statements)
references
References 34 publications
9
76
0
2
Order By: Relevance
“…[5,6] An alternate technology to produce biofuels from microalgal oil is through hydrotreating with Ni, Co and Mo sulfides or noble metal catalysts such as Pd and Pt supported on metal oxides. [7][8][9][10][11][12][13][14] While the high price of the noble metals can be avoided by using the sulfided catalysts, slow desulfurization reduces their activity and contaminates the fuel. [7,9,15] Furthermore, these catalysts have shown poor selectivity, favoring cracking and decarbonylation over hydrodeoxygenation to produce broad hydrocarbon distributions.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] An alternate technology to produce biofuels from microalgal oil is through hydrotreating with Ni, Co and Mo sulfides or noble metal catalysts such as Pd and Pt supported on metal oxides. [7][8][9][10][11][12][13][14] While the high price of the noble metals can be avoided by using the sulfided catalysts, slow desulfurization reduces their activity and contaminates the fuel. [7,9,15] Furthermore, these catalysts have shown poor selectivity, favoring cracking and decarbonylation over hydrodeoxygenation to produce broad hydrocarbon distributions.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that 1% Pt/TiO2 displayed a higher C8 hydrocarbon selectivity than 1% Pt/Al2O3. This was attributed to the presence of larger oxygen vacancies on the TiO2 support [59]. Results of a similar screening study for the decarboxylation of stearic acid are depicted in the figure (11).…”
Section: Methyl Estermentioning
confidence: 87%
“…For example, in deoxygenation of methyl stearate and methyl octanoate over alumina-supported Pt [59], 1% Pt/γ-Al2O3 reported to be highly active and selective toward deoxygenation. They reported that 1% Pt/TiO2 displayed a higher C8 hydrocarbon selectivity than 1% Pt/Al2O3.…”
Section: Methyl Estermentioning
confidence: 99%
“…In inert gas He, the condensation products (diphenylketone and octyloctanoate) were observed by esterification and ketonization. In contrast, when this reaction was carried out in H 2 , mostly paraffins (mainly C 7 and C 8 hydrocarbons) were obtained 25 . Catalytic deoxygenation of palmitic and stearic acids mixture was studied over four synthesized Pd catalysts supported on synthetic carbon (Sibunit) in a semi-batch reactor at 260-300 °C using dodecane as a solvent.…”
Section: F I G 1 -Transesterification Of Triglyceridesmentioning
confidence: 91%